The Significant Impact of Programmed Cell Death-1 Gene Polymorphism on HBV Infection and Viral Load - Hiba Hadi Rashid; Hiba M. Al-Darraji; Müge FIRAT; Bassam Mohammed Mishkhal (Diyala Journal of Medicine, 2025)
Background: Hepatitis B virus (HBV) is a common and international problem associated with severe liver diseases. Programmed cell death-1 (PCD-1) is an immunosuppressive molecule that negatively regulates T-cell activity. Genetic variation in PCD-1 gene could impact the encoded protein, and, thus HBV infection. Objective: To assess the single nucleotide polymorphisms (SNPs) in the PCD-1 gene's promotor area effect of viral load and HBV infection. Patients and Methods: This case-control study recruited 117 subjects (67 patients with HBV and 50 apparently healthy persons as control). From June 2024 to November 2024, all subjects had been selected at the Gastroenterology and Liver Hospital-Medical City (Baghdad, Iraq). Every participant donates about 5 mL of blood extracted from a vein and stored at -80 °C until it was needed. Blood samples were used to obtain genomic DNA, and gene fragment corresponding the rs38084323 polymorphism in PCD-1 gene was amplified and genotyping by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Results: The patients' and controls' mean ages did not differ significantly, out of the 67 patients, 39 (43.28%) had an acute infection, and 38 (56.7%) had a chronic infection. Merely 34.33% of the patients were receiving HBV-specific therapy. Patients having the mutant homozygous genotype (GG) of rs38084323 were significantly more likely to have it (28.36% vs. 14%) (OR= 3.34, 95%CI= 1.07-10.38, p= 0.037). On the level with allele, the G allele was more often found in patients than in healthy subjects (54.48% vs. 41%), demonstrating an important disparity (OR=1.72, 95% CI=1.02-2.91, p=0.042). The various genotypes did not substantially affect the progression of infection to a chronic status. Although, 30.77% of patients carrying the AA genotype had viral ≥ 200000 IU/ml compared with 5.71% for AG carriers and 15.79% for GG carries with such a viral load, and these results were shown significant difference. Conclusion: The homozygous mutant genotype (GG) and G allele may be regarded as an indicator of risk for HBV infection. However, their impact on viral load is negligible. Keywords: Hepatitis B virus, Programmed cell death-1, Promoter, Single nucleotide polymorphism, Apoptosis.